3-Nitro-2-pyridinesulfenyl-mediated solid-phase disulfide ligation in the synthesis of disulfide bond-containing cyclic peptides. Issue 11 (6th February 2015) - Taguchi, Akihiro; Fukumoto, Kentarou; Asahina, Yuya; Kajiyama, Akihiro; Shimura, Shunsuke; Hamada, Keisuke; Takayama, Kentaro; Yakushiji, Fumika; Hojo, Hironobu; Hayashi, Yoshio
Abstract : A new solid-phase disulfide ligation method is developed to prepare a disulfide peptide from two types of Cys-containing peptide fragments with minimum purification steps. Abstract : A new solid-phase disulfide ligation method is developed to prepare a disulfide peptide from two types of Cys-containing peptide fragments with minimum purification steps. In combination with the subsequent intramolecular amide bond formation, a cyclic nonapeptide, oxytocin, was efficiently synthesized as a fundamental model for more complex cyclic peptides.